KONFLIK PADA GRUP DISKUSI MAHASISWA SAAT PEMBELAJARAN JARAK JAUH - Nurul Retno Nurwulan; Annisa Nurhayati; Maya Primeradama Yanti; Rezky Aryani Putri; Utari Trinita; Putra Elnandha Varza (STKIP PGRI SITUBONDO, 2021)
All learning activities in Indonesia during COVID-19 pandemic are conducted through online remote learning. However, it does not change the nature of the learning activities because homework, group project, and exams still need to be done by the students. The group discussion is more difficult since all communications between members need to be done online. This study aimed to evaluate the prevalence of conflict in college students’ group discussions. A total of 100 college students was recruited in this study. Based on the analyses from the collected questionnaire, it can be seen that the incompetent group leader (p = 0.003), misunderstanding in online communication (p = 0.047), lack of group discussion (p = 0.001), and selfishness of the members (p = 0.001) significantly affect conflict the group discussion. To avoid the conflict, it is suggested that all members need to always attend the online discussion and actively participate in the discussion to minimize misunderstanding.